Tax prevention audit and impact on the payment of the general tax on sales in footwear companies - Castillo del Águila, Greta Magaly (2021)
Objective: To determine to what extent the application of the tax preventive audit affected the General Sales Tax payment in footwear companies in Trujillo in 2017. Method: The investigation was quantitative, and it was developed with the information of three footwear companies from the Association of Small Industrialists and Artisans of Trujillo. The accountants of each company were subjected to the questionnaire survey technique, to the documentary analysis, and to a series of interview Results: The tax preventive audit in footwear companies decreased by 66.7% in both, the tax non-compliance of the General Sales Tax, and the audits of the National Superintendency of Customs and Tax Administration in 2017. Conclusion: The preventive tax’s audit applied to footwear companies in Trujillo, significantly reduced the payment deficit of the General Sales Tax for the year 2017.